International legal standards for the protection of human rights in the field of law enforcement: experience of implementation in the law and order of Ukraine - Kulyk, Serhii; Gavrylenko, Volodymyr; Anisimova, Maryna Fedorivna; Hafych, Ivan; Kuzmych, Sergii (Observatory of Foreign Relations, Universidade Autónoma de Lisboa, Portugal., 2026)
Policing in Ukraine must comply with international legal standards to protect human rights, which is a key requirement of the global community and a necessary condition for European integration. At the same time, the practical implementation of these standards remains problematic due to legislative gaps, personnel difficulties, and insufficient control mechanisms, which require further scientific analysis and improvement of law enforcement practice. The study uses methods of analysis, synthesis, induction, deduction, dialectics, analogy, abstraction, and generalization. The aim of the research is to analyze human rights protection standards in the activities of law enforcement agencies, to assess their implementation in Ukraine, and to develop recommendations for improving national legislation and practice of police agencies. Significant progress in bringing Ukrainian law enforcement in line with international legal norms has been made, but persistent challenges require continuous adaptation and policy improvement. Strengthening institutional mechanisms, enhancing public scrutiny and promoting international cooperation will be crucial to ensure sustainable compliance with human rights standards.
Keywords: human rights; institutional mechanisms; policy adaptation; public oversight; law; права людини; інституційні механізми; адаптація політики; громадський контроль; право